Identification of Angiotensin-Converting Enzyme Inhibitory Proteins from Mycelium of Pleurotus pulmonarius (Oyster Mushroom) - Ibadallah, Badjie Xietaqieuallah; Abdullah, Noorlidah; Shuib, Adawiyah Suriza (Planta Medica, 2015)
Pleurotus pulmonarius (grey oyster mushroom) has been acknowledged as a recuperative agent for many diseases in addition to its recognition as a nutritious provision. We performed a study on P. pulmonarius mycelium for an antihypertensive effect via the angiotensin-converting enzyme inhibitory activity. The preliminary assay on the mycelial water extract demonstrated that the angiotensin-converting enzyme inhibitory activity had an IC50 value of 720 µg/mL. Further protein purifications via ammonium sulphate precipitation and RP-HPLC resulted in 60× stronger angiotensin-converting enzyme inhibitory activity than that of the mycelial water extract (IC50 = 12 µg/mL). Protein identification and characterisation by MALDI-TOF/TOF, later corroborated by LC-MS/MS, indicated three proteins that are responsible for the blood pressure lowering effects via different mechanisms: serine proteinase inhibitor-like protein, nitrite reductase-like protein, and DEAD/DEAH box RNA helicase-like protein.
Keywords: ACE inhibitor; bioactive protein; hypertension; fungi; Pleurotaceae; Pleurotus pulmonarius; oyster mushroom